English Language Training Assistance to Improve English Language Knowledge and Skills for Atv Ozzy Bali Adventure Employees - Rimadias, Santi; Ferli, Ossi; Lestariani, Ni Made (Jurnal Pengabdian Masyarakat Bestari, 2024)
In order to improve the ability of Human Resources (HR) in the field of tourism, especially in MSMEs ATV Ozzy Bali Adventure, a community service program was initiated with the main focus on providing assistance and English language training. The aim is to improve employees' knowledge and skills in utilizing English, thereby facilitating improved communication and improving the quality of service for foreign tourists. The two-day service initiative uses a variety of methods, including the delivery of Basic English content through lectures, discussions, Q&A sessions, and on-site mentoring. The results of this training can be seen from the increase in English language competence which can be seen from a significant increase in Post-Test scores compared to Pre-Test results. In addition, there was visible improvement in both verbal and non-verbal English usage skills among the four ATV Ozzy Bali Adventure employees involved in the program.